A comparative study of the acute toxicity of the herbicide atrazine to cladocerans Daphnia magna, Ceriodaphnia silvestrii and Macrothrix flabelligera - Moreira,Raquel Aparecida (2014)
AIM: In this study we compared the sensitivity of three species of Cladocera, Daphnia magna, Ceriodaphnia silvestrii and Macrothrix flabelligera, to the commercial product of the herbicide Atrazine, the Atrazine Atanor 50 SC® (500 g/L), widely used on crops in Brazil. METHODS: Acute toxicity tests were performed at the nominal atrazine concentrations 2.25, 4.5, 9.0, 18.0, 36 and 72 mg L-1, on C. silvestrii and M. flabelligera and at 2.25, 4.5, 9.0, 18.0, 36, 72 and 144 mg L-1 on D. magna. The range of concentrations tested was established in a series of preliminary tests. RESULTS: The toxicity tests showed that the two species naturally occurring in water bodies in Brazil were more susceptible than Daphnia magna. The effective concentrations of Atrazine Atanor 50 SC® (EC50- 48 h) to the species M. flabelligera, C. silvestrii and D. magna were 12.37 ± 2.67 mg L-1, 14.30 ± 1.55 mg L-1 and 50.41 ± 2.64 mg L-1, respectively. Furthermore, when EC50 observed here for M. flabelligera and C. silvestrii were compared with published values of EC50 or LC50 (mg L-1) for various aquatic organisms exposed to atrazine, it was seen that these two cladocerans were the most sensitive to the herbicide. CONCLUSIONS: Considering these results and the broad distribution of C. silvestrii and M. flabelligera in tropical and subtropical regions, it is concluded that these native species would be valuable test organisms in ecotoxicological tests, for the monitoring of toxic substances in tropical freshwaters.